2017
DOI: 10.1128/genomea.01196-17
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequence of the Fruiting Myxobacterium Cystobacter fuscus DSM 52655

Abstract: Among myxobacteria, the genus Cystobacter is known not only for fruiting body formation but also for formation of secondary metabolites, such as cystobactamids and cystothiazols. Here, we present the complete genome sequence of the Cystobacter fuscus strain DSM 52655, which comprises 12,349,744 bp and 9,836 putative protein-coding sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The Gram-negative Cystobacter genus is comprised of seven validly published species (available at: https://lpsn.dsmz.de/genus/cystobacter ) and although previous taxonomic studies have indicated that this genus belongs to the Archangiaceae family, a recent study by Waite et al (2020) proposed its reclassification as a member of the Myxococcaceae family, within the Myxococcales order. These myxobacteria are ubiquitous in soil environments and similar to Myxococcus species, Cystobacter utilise gliding motility to move over surfaces, and are also able to form spore-filled fruiting bodies when subjected to unfavourable conditions ( Akbar et al, 2017 ; Treuner-Lange et al, 2017 ). However, the Cystobacter fruiting bodies differ in morphology to those of the Myxococcus genus, and are shiny, spherical and held within a slime matrix, whereas the latter are characterised by haystack-shaped cell aggregates ( Treuner-Lange et al, 2017 ).…”
Section: Antimicrobial Lipopeptides: Production By Underexplored Pred...mentioning
confidence: 99%
See 1 more Smart Citation
“…The Gram-negative Cystobacter genus is comprised of seven validly published species (available at: https://lpsn.dsmz.de/genus/cystobacter ) and although previous taxonomic studies have indicated that this genus belongs to the Archangiaceae family, a recent study by Waite et al (2020) proposed its reclassification as a member of the Myxococcaceae family, within the Myxococcales order. These myxobacteria are ubiquitous in soil environments and similar to Myxococcus species, Cystobacter utilise gliding motility to move over surfaces, and are also able to form spore-filled fruiting bodies when subjected to unfavourable conditions ( Akbar et al, 2017 ; Treuner-Lange et al, 2017 ). However, the Cystobacter fruiting bodies differ in morphology to those of the Myxococcus genus, and are shiny, spherical and held within a slime matrix, whereas the latter are characterised by haystack-shaped cell aggregates ( Treuner-Lange et al, 2017 ).…”
Section: Antimicrobial Lipopeptides: Production By Underexplored Pred...mentioning
confidence: 99%
“…These myxobacteria are ubiquitous in soil environments and similar to Myxococcus species, Cystobacter utilise gliding motility to move over surfaces, and are also able to form spore-filled fruiting bodies when subjected to unfavourable conditions ( Akbar et al, 2017 ; Treuner-Lange et al, 2017 ). However, the Cystobacter fruiting bodies differ in morphology to those of the Myxococcus genus, and are shiny, spherical and held within a slime matrix, whereas the latter are characterised by haystack-shaped cell aggregates ( Treuner-Lange et al, 2017 ). Cystobacter species have a relatively large genome size, thus enabling them to produce a vast range of secondary metabolites, including bacteriocins, polyketides, lantipeptides and microcins ( Saadatpour and Mohammadipanah, 2020 ).…”
Section: Antimicrobial Lipopeptides: Production By Underexplored Pred...mentioning
confidence: 99%